Study on the genus Parastrangalis Ganglbauer, 1889 (Coleoptera, Cerambycidae, Lepturinae) from Shennongjia, China - Gu, Jiayi; Wang, Ping; Xie, Guanglin; Wang, Wenkai (Zootaxa, 2023)
Seven species of the genus Parastrangalis Ganglbauer, 1889 are recorded from Shennongjia Forestry District (China). Among them, a new species, P. shennongjiaensis sp. nov., is described and illustrated, and P. holzschuhi Chou & N. Ohbayashi, 2014 is reported for the first time from mainland China, P. houhensis N. Ohbayashi & Wang, 2004 and P. palpalis Holzschuh, 1991 are newly recorded from Shennongjia Forestry District, Hubei.